The language of the other and ours: Politics, translation and psychoanalysis - Souza Jr, Paulo Sérgio de (Estudos Avançados, 2021)
This paper starts with general linguistic-historical aspects and addresses the Brazilian case to reflect on the role of the vernacular as an instrument of colonization, and on language policy in Brazil. Because colonizing the other involves language, and because of the Brazilian linguistic, racial and socioeconomic specificities, we seek to bring to the debate some effects of colonization in a field where language has a doubly privileged status, namely: the translation of psychoanalytic texts.